Korelasi Penggunaan Kelambu dan Obat Nyamuk Serta Keberadaan Genangan Air terhadap Kejadian Malaria pada Daerah Endemik PT. Tandan Sawita Papua - Nia Ardyawati; Arif Rachman; Oke Andikarya (Pusat riset dan Inovasi Nasional, 2025)
Malaria is an infectious disease caused by Plasmodium parasites and transmitted through the bites of female Anopheles mosquitoes. It remains a serious public health issue in various endemic regions, particularly in developing countries. This study aims to identify the factors associated with malaria incidence and evaluate the effectiveness of prevention and control programs that have been implemented. A quantitative approach with a descriptive correlational research design was used, involving secondary data from the Health Office reports and primary data collected through field surveys in the endemic area of PT. Tandan Sawita Papua, Keerom Regency. The results showed that malaria incidence is associated with the use of mosquito nets and the use of mosquito repellents. The study concludes that an integrated approach to malaria control is essential, including community education, environmental improvements, and sustainable health policy support.